Circ_001042 Inhibits TGF-β1/P38 MAPK Signaling Axis-Mediated Epithelial-Mesenchymal Transition and Metastasis in Lung Adenocarcinoma. (4th August 2022) - Zhou, Lixia; Chen, Wenxian; Yang, Hang; Liu, Jiaqin; Meng, Hui
Abstract : Objective . To explore the role and molecular mechanism of circ_001042 in lung adenocarcinoma (LUAD). Methods . The expression level of circ_001042 and linear RNA MRPS35 in cells and clinical tissues was detected by real-time PCR (qRT-PCR). The expression of circ_001042 and transforming growth factor β 1 (TGF- β 1) in LUAD cells was elevated by the respective transfection of overexpression vectors OE-circ_001042 and TGF- β 1; MTT and transwell assays were applied to test the proliferation, migration, and invasion abilities of cells, respectively. The E-cadherin expression level in the cells was assessed by immunofluorescence staining, and western blot was utilized to determine the expression level of epithelial-mesenchymal transition (EMT) and TGF- β 1/P38 MAPK signaling axis-related proteins in the cells. Results . Circ_001042 was significantly downregulated in LUAD tissues and cells, and high circ_001042 expression could inhibit the proliferation, invasion, and migration of LUAD cells. In addition, circ_001042 also inhibited the EMT process (the E-cadherin level was upregulated; and the levels of N-cadherin, vimentin, and Snail were downregulated) and TGF- β 1/P38 MAPK signaling axis activity in LUAD cells. Moreover, circ_001042 could suppress the promotion of TGF- β 1 on the proliferation, invasion, migration, and EMT process of LUAD cells and the activation of TGF- β 1/P38 MAPK signaling axis. Conclusion . By inhibiting TGF- β 1, circ_001042 not only suppresses the proliferation, migration, invasion, and EMT of LUAD but also inhibits the activation of TGF- β 1/P38 MAPK signaling axis. Therefore, circ_001042 can act as a potential target for early diagnosis and targeted therapy of LUAD.